Immediate Placement of Dental Implant on Freshly Extracted Socket: A Case Report From B. P. Koirala Institute of Health Sciences, Dharan - Basnet, Bishal Babu (Birat Journal of Health Sciences, 2017)
Immediate placement of implants into the freshly extracted tooth sockets is viable and preferable option in many cases who have to wait for healing phase in traditional implant therapy. This has been a great boon for the implant dentistry. In this case a young lady who had unusual trauma to her upper front tooth had immediate implant placed on the same day of extraction and metal-ceramic crown restored her esthetics after about 4 months. With extensive treatment planning and execution of surgical and prosthetic phases of implant therapy, immediate placement of dental implant gives wonderful results. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, page: 230-233